PENGELOLAAN INFORMASI DIGITAL DALAM MENANGANI PERJUDIAN ONLINE DI INDONESIA - Muhajir, Muhammad Zaenal Muhajir; Yulyana, Eka; Aryani, Lina (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
Online gambling has become a serious problem in Indonesia, with an increase in gambling content reaching 5,128,871 pieces in the 2017-2024 period, of which 67.4% was addressed by 2024. This study aims to evaluate and analyze digital information management strategies used to address the problem of online gambling in Indonesia. This study applies a qualitative methodology through a single case study approach at the Directorate of Informatics Application Control (APTIKA) of the Ministry of Communication and Digital. Data collection was carried out through four main methods: observation, in-depth interviews, documentation, and literature study. Data analysis uses the Miles and Huberman model with the Defense In Depth information security theory from Coole & Brooks (2011) which consists of four aspects: governance, people, process, and technology. The results show that digital information management has been implemented with a strong operational structure through the implementation of regulations from the ITE Law, the PDP Law, and the PP PSTE, human resource capacity development through continuous training, the implementation of comprehensive SOPs with encryption technology and strict access control, and the use of advanced technology for monitoring and detection. Furthermore, there are still significant obstacles, particularly significant gaps in public communication and accessibility of information to the public, limited prevention education programs, and challenges in dealing with technological developments used by cybercriminals.